Meeting the challenge of (co-)designing real-world laboratories. Insights from the Well-Being Transformation Wuppertal project. - Rose, Michael; Maibaum, Katrin (ÖKOM, 2020)
As transdisciplinary and transforrnative research approaches, real-world laboratories (RwLs) come with many pitfalls. Their design and implementation place high demands an everyone involved, which means that realistically, things rarely go smoothly. This Design Report shares the lessons learned about establishing and adjusting communication and organisational structures in RwLs.
Keywords: Reallabor; Forschungsansatz; Forschungsbericht; Organisationsform; Kommunikationsstruktur; Pilotprojekt; Implementation